ANALYSIS OF GENETIC DIVERSITY OF PALM OIL PLANT (Elaeis guineensis Jacq.) PALM OIL RESEARCH CENTER (PPKS) BASED ON PRIMARY SSR (Simple Sequence Repeats) - Riski Aulia (Agripreneur : Jurnal Pertanian Agribisnis, 2021)
The background of this research was to obtain information of genetic diversity within and among populations of E. guineensis using SSR markers. This research was conduted in Biology Molecular Laboratory, Indonesian Oil Palm Research Institute, Marihat, Pematangsiantar, North Sumatra from March 2016 to January 2017. A total of 100 palm oil samples used in this research, including 20 samples from the populations of E. guineensis TR01S, including 20 samples from the populations of E. guineensis BJ022S, including 20 samples from the populations of E. guineensis BJ42S, including 20 samples from the populations of E. guineensis BO52S, and including 20 samples from the populations of E. guineensis MA19S. Calculation and Desciptive analysis in this research using software GeneMarker® version 2.40, software DARwin version 6.0.13 and Microsoft Excel 2007. Research shows that the number of banding patterns detected 104 The banding patterns WITH range 8-9 per primary banding pattern, and the size of the banding patterns ranging from 101 bp -328 bp. mEgCIR2569 primary is the most widely primer to amplify DNA and the average of the percentage of polymorphism in the primer being used by 71%. Analysis dendogram 100 samples All 3 hearts big group of Jatropha genetic WITH BETWEEN Yang ranged from 0.03 to 1.00 Based on the findings of the analysis of genetic relationships WITH Matrix Method using differences Simple Matching Value factorial analysis (PCoA) declared WITH axis I and axis II ON 12 primary SSR of 20.3%. mEgCIR2569 primary is the most widely primer to amplify DNA and the average of the percentage of polymorphism in the primer being used by 71%. Analysis dendogram 100 samples All 3 hearts big group of Jatropha genetic WITH BETWEEN Yang ranged from 0.03 to 1.00 Based on the findings of the analysis of genetic relationships WITH Matrix Method using differences Simple Matching Value factorial analysis (PCoA) declared WITH axis I and axis II ON 12 primary SSR of 20.3%. mEgCIR2569 primary is the most widely primer to amplify DNA and the average of the percentage of polymorphism in the primer being used by 71%. Analysis dendogram 100 samples All 3 hearts big group of Jatropha genetic WITH BETWEEN Yang ranged from 0.03 to 1.00 Based on the findings of the analysis of genetic relationships WITH Matrix Method using differences Simple Matching Value factorial analysis (PCoA) declared WITH axis I and axis II ON 12 primary SSR of 20.3%.